UNLOCKING THE POTENTIAL OF Chlorella sp. FOR BTEX REMOVAL: AN INNOVATIVE APPROACH TO BIOREMEDIATION - Cárdenas García, Jaime Dante (2024)
BTEX aromatic hydrocarbons (benzene, toluene, ethylbenzene and xylene) are persistent and toxic pollutants from industrial activities and oil spills that significantly affect water and soil quality as well as human health. Given the limitations of physicochemical methods for the remediation of these contaminants, bioremediation, particularly through the use of microalgae such as Chlorella sp., emerges as an efficient and sustainable alternative due to its ability to biodegrade contaminating organic compounds and adapt to various environmental conditions. Hence, this study evaluated the efficiency of BTEX hydrocarbon biopurification using the microalgae Parachlorella kessleri, isolated and morphologically and molecularly characterized. Its growth kinetics were determined, obtaining an exponential phase of 120 hours, a specific growth rate μ=0.0230 h⁻¹ and a generation time G=30.15 h. Measurement of BTEX by FID gas chromatography showed high precision and selectivity, with minimum detectable concentrations for benzene of 0,4 mg/L, toluene 1,7 mg/L, ethylbenzene 4,7 mg/L, and xylenes between 1,4-7,2 mg/L. Parachlorella kessleri demonstrated a remarkable bioremediation capacity, removing up to 93,6% of benzene, 78,1% of toluene, 66,0% of ethylbenzene and up to 73,7% of xylenes in five days. These results highlight the enormous potential of microalgae in mitigating growing environmental pollution and sets an invitation to reevaluate the role of biotechnology to sustainably address contemporary global environmental challenges.